Chemical Control of Alternaria Brown Spot on Mandarins Cultivars in Tunisia - Haddad, Maali; Benfradj, Najwa; Salem, Ibtissem Ben; Boughalleb-M’Hamdi, Naima (Review of Plant Studies, 2020)
Three field experiments were conducted to evaluate the efficiency of seven active ingredients (Tryfloxystrobin, Iprodione, Procymidone, Mancozebe, Propinebe, Tebuconazole and Coppersulfate), against Alternaria brown spot (ABS) caused by Alternaria alternata on Minneola, Fortune, Nova and Tangerine mandarins citrus cultivars in Tunisia. Over the three trials, citrus trees received 6, 10 and 16 fungicides sprays. The results of the present investigation demonstrated the prevention ability of Mancozebe, Iprodione and Copper sulfate according to disease incidence, fruit infection and losses caused by ABS. Furthermore, the applications of those three fungicides used in mixture reduce the ABS development. In fact, disease incidence was reduced better after an application of a mixture of Mancozebe and Iprodione compared to application of Mancozebe or Iprodione alone and after an application of an alternation of Mancozebe and Iprodione with copper sulfate. From this study, it revealed that the incidence of ABS, an emerging fungi disease on Citrus in Tunisia, could be reduced by using chemical products.